The Effect of Single Bout of Competitive Training on Muscle Damage and Liver Enzymes in University Student Wrestling and Taekwondo Athletes - Karaman, Muhammed Emre; Arslan, Cengiz; Kinaci, Ayse Eda (Sciencedomain Int, 2021)
Aims: The effects of exercise/training on biochemical parameters may vary according to the characteristics of individuals, physical conditions, duration and intensity of exercise, and different lipid values. The purpose of this study was to investigate the alterations in muscle damage and liver enzyme parameters of male university student wrestling and taekwondo athletes after single bout of competitive training. Methodology: The participants of the present study, sampled voluntarily. The research sample consists of 6 elite level male wrestlers (age=17.33 +/- 0.54) and 6 elite level male taekwondo (age=17.66 +/- 0.54) athletes. First of all, blood samples from all athletes were taken to evaluate the pre-test levels of serum AST, ALT and CK. After 15 minutes of warm-up, in accordance with the competition conditions of the relevant sports branch, the match was made in a total of 6 minutes, with appropriate loading intensity and rest interval. After at least 15 minutes of training blood samples were taken again to evaluate the post-test levels of AST, ALT and CK. Serum samples were studied in an auto analyzer. Results: The results showed that after single bout of competitive training, serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatine kinase (CK) significantly increased in both groups ( p<0.05). Conclusion: As a conclusion; acute load of exercise caused an increase in both muscle damage and liver enzyme parameters. When this increase is compared between the two combat sports, it was seen that the parameters of the wrestlers were higher. If these biomarkers increase so much during competition, this will negatively affect the athletic performance of the athletes. In order to prevent this, success can be achieved by ensuring that the athletes are trained sufficiently and prepared for the competition during the pre-competition preparation period.
Keywords: Single bout of exercise; university student athletes; liver enzymes; muscle damage enzyme; wrestling; taekwondo